Sleep deprivation models in rodents - Nur Syafiqah Mohmed Nor; Afifah Nawi; Wan Amir Nizam Wan Ahmad; Liza Noordin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sleep deprivation has been identified as a risk factor for various diseases. The number of patients suffering from sleep deprivation is increasing daily. Therefore, the risk to develop various diseases, including cardiovascular disease is increasing. However, there is a limitation to elucidate the pathophysiological changes following sleep deprivation in humans. Thus, the need arises for sleep deprivation models using animals, which will serve the purpose of understanding the disease in a better way. Several techniques have been developed to model sleep deprivation in animals, including inverted flowerpot and multiple platforms techniques. Genetic and environmental factors, costs, infrastructure and animal life spans are some of the factors that need to be considered when selecting a particular model. Furthermore, when studying sleep deprivation, tissue samples, such as peripheral blood, brain samples and aorta are used to elucidate the underlying mechanisms of a particular disease. Currently, more than ninety percent of all laboratory animal experiments are performed in rats and mice. This review article focuses on models of sleep deprivation in Rodents, which are generally used in research laboratories. The article also tries to evaluate the advantages and disadvantages of each technique discussed, guides the sleep deprivation model and helps researchers to decide on a specific model for their purpose.